Freedom of thought and anonymous reporting (Revista do Tribunal Regional Federal da 3ª Região, 2011)
The 1988 Federal Constitution guarantees the free expression of thought, stating in item IV of article 5: “The expression of thought is free, anonymity being prohibited.” It is true that anyone has the right to express an opinion on matters of state and society, and to do so they can publish manifestos and statements, give interviews, expose their points of view and, why not, expose the occurrence of any criminal offense to the competent police authority. In prohibiting anonymity, the Original Constituent Power intended to cover all forms of anonymity, including anonymous reporting of criminal offenses. There is no doubt that the prohibition of anonymity, which includes the concealment of those who express themselves by reporting a criminal offense, was intended to avoid any kind of affront to personality rights, such as intimacy, privacy, honor and image of the person reported, in addition to possible criminal liability for false reporting of a crime (CP, art. 340). It is correct to say that crimes cannot/should not go unpunished and that society aims to achieve justice, but in order to do so, it must be done in such a way that civilizational values, which are essential in a democratic society, are not offended by a “hidden” person belonging to the same society. The fact that any anonymous complaint is effective, with the discovery of the authorship and materiality of a prohibited legal model of conduct, through the opening of an investigation by the competent police authority, does not remove the violation of anonymity, determined by the Original Constitution.
Keywords: freedom of thought×anonymous tip×criminal offense×police investigation×evidence×; freedom of thought; anonymous tip; criminal offense; police investigation; evidence